P102 CLEVER-1 mediates the transmigration of B cells across human hepatic sinusoidal endothelium. (6th September 2011) - Shetty, S; Weston, C; Oo, Y; Stamataki, Z; Salmi, M; Jalkanen, S; Lalor, P; Adams, D
Abstract : Introduction: Lymphocytes are recruited via the unique hepatic sinusoidal channels during chronic inflammatory liver diseases. This low shear vascular bed is lined by hepatic sinusoidal endothelium (HSEC) which lacks certain conventional adhesion molecules leading us to look for novel receptors involved in lymphocyte recruitment. HSEC express several scavenger receptors including CLEVER-1 which we have recently shown mediates regulatory T cell recruitment to HSEC. B cells have been implicated in the pathogenesis of liver disease and driving liver fibrosis. Aim: B cells must be recruited from the peripheral circulation into liver tissue but the molecular mechanisms that mediate this process are not known. Our aim was to study if CLEVER-1 plays a role in this process. Method: We used isolated HSEC in flow adhesion assays to study the functional role of CLEVER-1 in lymphocyte subset recruitment. Immunofluorescent staining and confocal microscopy were used to characterise the transmigration of lymphocytes across HSEC under conditions of flow. Time lapse video recordings and Image J software was used to compare T cell and B cell recruitment via HSEC monolayers under conditions of flow. Results: Flow-based adhesion assays using human HSEC demonstrated that B cells were captured from flow and adhered to human HSEC but they had limited motility in comparison to T cells. B cells also underwent transmigration and CLEVER-1 blockade led to a reduction of B cells undergoing transmigration. Blockade of CLEVER-1, VAP-1 and ICAM-1 in combination had a cumulative effect on transmigration, suggesting that all three receptors contributed to B cell transmigration. Conclusion: Up to now most interest has focused on the role of T cells but hepatic infiltrates contains B cells and B cells have been directly implicated in models of liver disease and as drivers of liver fibrosis. This work demonstrates that CLEVER-1 is an adhesion molecule within the hepatic sinusoids and contributes to B cell transmigration. CLEVER-1 is a potential target for modulating B cell recruitment to the human liver.